The Effect of Brand Experience and Brand Love on Brand Loyalty of iPhone Products in Malang City - Rupianti, Reni; Adilla, Nur (International Conference on Digital Business Innovation and Technology Management (ICONBIT), 2024)
This study aims to examine the effect of brand experience and brand love on brand loyalty for iPhone products in Malang City. In the highly competitive technology industry, the influence of brand experience and brand love on brand loyalty is an important factor in retaining consumers. This research uses a quantitative approach with a sample of 136 Gen Z consumers who use iPhone products in Malang City. Data were collected through questionnaires which were processed using multiple linear regression analysis and processed through SPSS. The results showed that both brand experience and brand love have a significant effect on brand loyalty, with brand experience having a greater influence than brand love. This research provides an important contribution for marketers in designing strategies to increase customer loyalty to iPhone products, especially among Gen Z in Malang City.